A randomized controlled trial evaluating recovery and survival of 6% dimethyl sulfoxide–frozen autologous platelets in healthy volunteers. Issue 1 (7th June 2012) - Dumont, Larry J.; Cancelas, Jose A.; Dumont, Deborah F.; Siegel, Alan H.; Szczepiorkowski, Zbigniew M.; Rugg, Neeta; Pratt, P. Gayle; Worsham, D. Nicole; Hartman, Elizabeth L.; Dunn, Susan K.; O'Leary, Margaret; Ransom, Janet H.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: Availability of platelets (PLTs) is severely limited by shelf life in some settings. Our objective was to determine and compare to Food and Drug Administration (FDA) criteria the PLT recovery and survival of autologous PLTs cryopreserved at −65°C or less in 6% dimethyl sulfoxide (DMSO) reconstituted with a no‐wash method (cryopreserved PLTs [CPPs]) compared to autologous fresh PLTs. STUDY DESIGN AND METHODS: This was a randomized, Phase I study analyzing PLT viability and in vitro function in consenting healthy subjects. Apheresis PLTs (APs) were collected in plasma. APs were suspended in 6% DMSO, concentrated, and placed at not more than −65°C for 7 to 13 days. Frozen CPPs were thawed at 37°C and resuspended into 25 mL of 0.9% NaCl. Control PLTs (fresh autologous) and CPPs were labeled with 111In or 51Cr, and recovery and survival after reinfusion were determined using standard methods. A panel of in vitro assays was completed on APs and CPPs. RESULTS: After frozen storage, CPPs retained 82% of AP yield and showed increased PLT associated P‐selectin and reduced responses to agonists. CPP 24‐hour recovery (41.6 ± 9.7%) was lower than for fresh PLTs (68.4 ± 8.2%; p < 0.0001) and did not meet the current FDA criterion. CPPs had diminished survival compared to fresh PLTs (7.0 ± 2.1 days vs. 8.4 ± 1.2 days, respectively; p = 0.018), but did meet and exceed the FDA criterion for survival. CONCLUSION: While 24‐hour recovery does not meet FDA criteria for liquid‐stored PLTs, the CPP survival of circulating PLTs was surprisingly high and exceeded the FDA criteria. These data support proceeding with additional studies to evaluate the clinical effectiveness of CPPs.